O turismo de resorts e o desenvolvimento do litoral sul da Paraíba - Brito, Bruno Dantas Muniz de (2012)
The context in which the tourist activity has been developed stands out for the arrival of large hotels on the southern coast of Paraíba. This study aims to examine the implications of tourism resort about the development in the Jacumã district. The survey methods included a researched with leading sites in order to find out the news on the actions taken by tourism in the study area, as well as interviews with those involved in tourism development in the locality. Data were analyzed using content analysis technique. The results based on the categories of analysis "Jacumã Tourism Development" and "Tourist Resorts in Jacumã" show that the tourism resorts has not brought significant level of local development, considering that the problems encountered in infrastructure have not been mitigated Jacumã or even discussed seeking a solution. The study concludes that although it would appear the growth of tourism in the region the speeches made by local hegemonic agents assume a cyclical bias, because they realize the awakening to tourism, there is awareness that is necessary to change the current situation in. However, there are no actions in the medium or long term that may solve the obstacles and difficulties experienced by the population and needed to expand the development by the local trade. In this sense, it is believed that the interests are primarily anchored in the perspective of growth and not local development through tourism.